Fatigue in sarcoidosis and idiopathic pulmonary fibrosis: differences in character and severity between diseases - Atkins, Christopher Peter; Gilbert, Daniel; Brockwell, Claire; Robinson, Sue; Wilson, Andrew Malcolm (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Sarcoidosis and idiopathic pulmonary fibrosis (IPF) are two common forms of interstitial lung disease. Fatigue is a recognised feature of sarcoidosis but an association between IPF and fatigue has not been investigated. Rationale: To investigate the frequency and severity of fatigue in these groups, and variables affecting fatigue scores. Methods: A cross-sectional questionnaire study of patients with sarcoidosis and IPF followed-up at a single hospital was undertaken. Questionnaire data included validated measures of fatigue, anxiety, depression, sleepiness and dyspnoea, plus measures of disease severity including spirometry data. Results: Questionnaires were administered to 232 patients (82 healthy volunteers, 73 sarcoidosis patients and 77 IPF patients). Sarcoidosis patients had statistically higher sleepiness scores but no significant difference was seen between overall measures of fatigue, anxiety or depression. Stratification by severity revealed a non-statistically significant tendency towards more severe fatigue scores in sarcoidosis. Regression analysis failed to identify any significant predictor variables measured in the sarcoidosis cohort, though in the IPF group both dyspnoea and sleepiness scores were significant predictors of fatigue (R2=0.74). Conclusions: Both sarcoidosis and IPF patients suffer with fatigue, although sarcoidosis patients tended towards reporting more severe fatigue scores, suggesting a subgroup with severe fatigue. The fatigue experienced by the two groups appears to be different; sarcoidosis patients report greater frequency of mental fatigue whereas IPF patients appear to suffer exhaustion, potentially related to dyspnoea. Dyspnoea and sleepiness scores modeled the majority of fatigue in the IPF group, whereas no single factor was able to predict fatigue in sarcoidosis.